Controversies in Vitamin D: A Statement From the Third International Conference. (10th November 2020) - Giustina, Andrea; Bouillon, Roger; Binkley, Neil; Sempos, Christopher; Adler, Robert A; Bollerslev, Jens; Dawson‐Hughes, Bess; Ebeling, Peter R; Feldman, David; Heijboer, Annemieke; Jones, Glenville; Kovacs, Christopher S; et al.
Abstract: The Third International Conference on Controversies in Vitamin D was held in Gubbio, Italy, September 10–13, 2019. The conference was held as a follow‐up to previous meetings held in 2017 and 2018 to address topics of controversy in vitamin D research. The specific topics were selected by the steering committee of the conference and based upon areas that remain controversial from the preceding conferences. Other topics were selected anew that reflect specific topics that have surfaced since the last international conference. Consensus was achieved after formal presentations and open discussions among experts. As will be detailed in this article, consensus was achieved with regard to the following: the importance and prevalence of nutritional rickets, amounts of vitamin D that are typically generated by sun exposure, worldwide prevalence of vitamin D deficiency, the importance of circulating concentrations of 25OHD as the best index of vitamin D stores, definitions and thresholds of vitamin D deficiency, and efficacy of vitamin D analogues in the treatment of psoriasis. Areas of uncertainly and controversy include the following: daily doses of vitamin D needed to maintain a normal level of 25OHD in the general population, recommendations for supplementation in patients with metabolic bone diseases, cutaneous production of vitamin D by UVB exposure, hepatic regulation of 25OHD metabolites, definition of vitamin D excess, vitamin D deficiency in acute illness, vitamin D requirements during reproduction, potential for a broad spectrum of cellular and organ activities under the influence of the vitamin D receptor, and potential links between vitamin D and major human diseases. With specific regard to the latter area, the proceedings of the conference led to recommendations for areas in need of further investigation through appropriately designed intervention trials. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.